2004
DOI: 10.1007/s10630-005-0013-1
|View full text |Cite
|
Sign up to set email alerts
|

Trapping blockage of muscle nicotinic cholinoreceptors by mecamilamine

Abstract: Nicotinic cholinergic receptors can be blocked by both competitive and noncompetitive blocking agents of cholinoreceptors interacting with different regions of ionic channels [1]. Noncompetitive blocking agents may be divided into two subgroups: simple blocking agents of open channels and trapping blocking agents, which were originally described for glutamate receptors [2][3][4][5]. Earlier, we showed in the study on chromaffin rat cells that mecamilamine, a well-known neuronal blocking agent of channels, bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Based on these results, (±)-mecamylamine binds better to the recently activated AChR, and consequently it might inhibit ion flux by maintaining the receptor in this blockade state for longer time (decreasing the fraction of activated ion channels), or alternatively by inducing receptor desensitisation. The former possibility is consistent with the trapping blocking mechanism described for (±)-mecamylamine in different AChR subtypes 8,9 , whereas the latter possibility is ruled out based on the fact that (±)-mecamylamine does not increase [ 3 H]cytisine binding to Torpedo AChRs in the resting but activatable state ( Figure 4A), opposite to that observed for other desensitising NCAs 14,16 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Based on these results, (±)-mecamylamine binds better to the recently activated AChR, and consequently it might inhibit ion flux by maintaining the receptor in this blockade state for longer time (decreasing the fraction of activated ion channels), or alternatively by inducing receptor desensitisation. The former possibility is consistent with the trapping blocking mechanism described for (±)-mecamylamine in different AChR subtypes 8,9 , whereas the latter possibility is ruled out based on the fact that (±)-mecamylamine does not increase [ 3 H]cytisine binding to Torpedo AChRs in the resting but activatable state ( Figure 4A), opposite to that observed for other desensitising NCAs 14,16 .…”
Section: Discussionsupporting
confidence: 83%
“…The involved acetylcholine receptor (AChR) subtypes and mechanisms underlying these pharmacologic activities have not been clearly demonstrated yet. Additional results indicate that the pharmacological and clinical activities of mecamylamine are more complex than previously thought [2][3][4][5][6][7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of partial reversible deblocking of the channels is typical of trap-type blockers of open channels under conditions where activation of the receptors is combined with depolarization of the membrane [13,18,19]. In our study, we initially measured the amplitude of current responses of С2С12 cells to periodic (0.5 min -1 ) application of 1 μM ACh against the background of the action of 10 μM MA at a membrane potential of -70 mV (first signal in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In studies of cells of the submandibular ganglion with the use of a trap-type blocker, hexamethonium, it was first demonstrated that the phenomenon of partial reversible deblocking under conditions of agonist-induced activation of receptors combined with depolarization of the membrane does exist, and this phenomenon is typical of such a mode of blockade [13]. Studies on rat chromaffin cells [18] and neuromuscular junctions of the frog [19] demonstrated that it is exactly a trap-type mechanism that underlies the MA-induced blockade of cholinoreceptors of neuronal and muscle types.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, mecamylamine is trapped within the channel. In order for mecamylamine to exit the channel, the agonist must bind to the agonist recognition site in an orthosteric manner to produce a conformational change, returning the receptor to the open channel state (Gurney and Rang, 1984; Lingle, 1983; Skorinkin et al, 2004). A caveat of these studies is that they were performed in either non-neuronal (chromaffin cells) or neuromuscular models, and the interpretation of the results extrapolated to suggest a trapping mechanism for mecamylamine at nAChRs in the CNS.…”
Section: 0 Neuropharmacologymentioning
confidence: 99%